Takotsubo cardiomyopathy as an overlooked cause of cardiac arrest in a patient undergoing ureteral stenting: a case report and literature review. Issue 5 (May 2022) - Xu, Yue; Liu, Meinv; Li, Jianli; Rong, Junfang
Takotsubo cardiomyopathy (TC) is a rare disease with unclear etiology that is characterized by wall motion abnormalities of the left ventricle. We report a 64-year-old woman who presented with cardiac arrest 6 hours after ureteral stenting, with no history of heart disease. Notably, she had a urinary tract infection preoperatively. TC was diagnosed with characteristic apical ballooning on the left ventriculogram. The hemodynamics and cardiac function recovered quickly within 1 day after conservative treatment and controlling the infection. TC should be considered when a patient presents with decreased cardiac function after ureteral stenting, especially in patients with potential concurrent infection. A review of the literature documenting cases of TC related to urological surgery in the past decade was conducted using PubMed. The results were summarized in a table.